Odpowiedź :
2a-5b+(7-3a-2b)= 2a-5b+7-3a-2b = -a-7b+7
4-14x-(2x²-5x+3)=4-14x-2x²+5x-3=1-9x-2x²
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=-2m+7n+6
(-4a³+7a²-1)-(2a²+3a-1)=-4a³+7a²-1-2a²+3a-1=-4a³+5a²-2+3a
(-xy+5y-x)-(xy+2x-y)=-xy+5y-x-xy-2x+y=-2xy+6y-3x
;)
4-14x-(2x²-5x+3)=4-14x-2x²+5x-3=1-9x-2x²
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=-2m+7n+6
(-4a³+7a²-1)-(2a²+3a-1)=-4a³+7a²-1-2a²+3a-1=-4a³+5a²-2+3a
(-xy+5y-x)-(xy+2x-y)=-xy+5y-x-xy-2x+y=-2xy+6y-3x
;)
2a-5b+(7-3a-2b)= 2a-5b+7-3a-2b= -1a-7b+7
4-14x-(2x²-5x+3)=4-14-2x²-5x+3=-9-2x²-5x
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=-2+7n+15
(-4a³+7a²-1)-(2a²+3a-1)=-4a³+7a²-1-2a²+3a-1=-4a³-5a²-1
(-xy+5y-x)-(xy+2x-y)=-xy+5y-x-xy+2x-y=4y+x
chyba tak ;p;p
4-14x-(2x²-5x+3)=4-14-2x²-5x+3=-9-2x²-5x
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=-2+7n+15
(-4a³+7a²-1)-(2a²+3a-1)=-4a³+7a²-1-2a²+3a-1=-4a³-5a²-1
(-xy+5y-x)-(xy+2x-y)=-xy+5y-x-xy+2x-y=4y+x
chyba tak ;p;p
2a-5b+(7-3a-2b)=2a-5b+7-3a-2b=a-7b+7
4-14x-(2x²-5x+3)=4-14z-2x²+5x-2=2x²+5x-3=2x²-9x-1
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=2m+7n-14
(-4a³+7a²-1)-(2a²+3a-1)-4a³+7a²-1-2a²-3a+1=-4a³+5a²-3a
(-xy+5y-x)-(xy+2x-y)= -xy+5y-x-xy+2x+y=-x+6y-2xy
4-14x-(2x²-5x+3)=4-14z-2x²+5x-2=2x²+5x-3=2x²-9x-1
-(6st+2s)+4st+2s=-6st-2s+4st+2s=-2st
(3m+8n-9)+(15-5m-n)=3m+8n-9+15-5m-n=2m+7n-14
(-4a³+7a²-1)-(2a²+3a-1)-4a³+7a²-1-2a²-3a+1=-4a³+5a²-3a
(-xy+5y-x)-(xy+2x-y)= -xy+5y-x-xy+2x+y=-x+6y-2xy